Air rifle injury to the oropharynx. The essential role of computed tomography in deciding on surgical exploration. Issue 2 (1st March 2000) - Hung, T; Huchzermeyer, P; Hinton, A E
Abstract : Gunshot wounds specific to the oropharynx are extremely rare with no reported cases of such injury in the world literature. The importance of such cases rests on the use of modern imaging techniques including computed tomography, magnetic resonance imaging, and vascular imaging in the making of management decisions and particularly in deciding the need for exploration of such an injury. In our case a conservative approach was adopted in view of the computed tomography finding and the stable clinical condition of the patient.